Enforcement of criminal offences in terms of the National Water Act 36 of 1998 - Agbonjinmi, Ayodeji Peter (University of Limpopo, 2007)
The purpose of this thesis was to critically examine the enforcement of environmental regulations with special reference to the enforcement of offences in the National Water Act 36 of 1998. “Enforcement” was conceptualized as “power” the exercise of which is constrained by the constitutionally guaranteed rights, especially the rights contained in Chapter 2 of the Constitution of the Republic of South Africa Act 108 of 1996 – the Bill of Rights. “Compliance” was conceptualized as a rational action. The polluter is both a rational economic actor as well as a rational political actor. “Enforcement” and “Compliance” were further considered as economic activities with costs and benefits. The “responsive enforcement and compliance” model was also adopted in this thesis. Environmental regulation is contentious because of the failure to adequately distinguish environmental crimes (mala prohibita) from common law crimes (mala in se) and the erroneous believe in the immutability of law especially pro-defendant procedural rights in criminal prosecution. This failure to distinguish environmental crimes from common law crimes resulted in the requirement of the proof of mens rea in criminal prosecution for breach of environmental law. Arguments were advanced to show that mens rea can easily be proved in environmental law areas of land use and development and resource conservation while it is a Herculean task for the prosecutor to prove mens rea in waste disposal and pollution offences. Arguments were also advanced, in terms of s. 24 of the 1996 Constitution and s. 2 of the National Environmental Management Act 107 of 1998, to show that “sustainable development” and the principles derived therefrom, especially the “precautionary principle” and the “polluter–pays principle”, are part of the corpus of South African constitutional and statutory laws. The “precautionary principle” and the “polluter-pays principle” have assumed the status of customary international law, and consequently part of South African laws in terms of s. 232 of 1996 Constitution. The provisions of s. 24(b) of 1996 Constitution prescribed both positive and negative duties for the state in respect of environmental regulation and prescribed the ambit of environmental regulation in South Africa. The “precautionary principle” is interpreted as deliberation guiding in form and a legal rule in content. The “precautionary principle” as a rule guides the actions of organs of state and other environmental stakeholders. The “polluter-pays principles” is interpreted as a legal rule which should be applied in the “all-or-nothing” sense. Arguments were advanced for the application of the “polluter-pays principles” in criminal prosecution. The legal effect of the application of “polluter-pays principle” in criminal prosecution for environmental crimes is to negative mens rea and transform environmental crimes to strict liability offences. In the environmental law areas of land use and development and resource conservation where mens rea is easily provable, the application of the “polluter-pays principle” would limit the prosecutor’s duty to proving, beyond reasonable doubt, the acts that constitute the offence against the accused. Thereafter, it is opened to the accused to prove, on scale of probabilities, that he lacks the mens rea (dolus or culpa) necessary for conviction. In the area of waste disposal and pollution control where proof of mens rea is difficult, the application of the “polluter-pays principle” should result in the application of the rule in Rylands Fletcher. All the prosecutor need do to obtain conviction is to prove, beyond reasonable doubt, the acts that constitute the offence against the accused. The Reconstruction and Development Programme (RDP) is identified and recognized as the dominant social paradigm (DSP) in South Africa. It is within the context of this DSP that environmental regulation is situated. Examining the penal provisions in the National Water Act 36 of 1998 against the background of the DSP, one is not left in doubt why the water pollution and degradation offences in the Act are fault-based. The DSP also partly accounts for the subordination of criminal law to administrative and civil judicial procedures in the enforcement of offences in the NWA 36 of 1998. Offences in the NWA 36 of 1998 were classified into 5 groups– failure crimes, reporting crimes, fraud crimes, obstruction crimes and environmental injury crimes. The failure crimes, reporting crimes, fraud crimes and obstruction crimes are common law crimes (mala in se) in the environmental law context, they are therefore subject to criminal prosecution like any other common law crime. Most of the environmental injury crimes are subject to administrative and civil judicial penalties, that is, the criminal sanction is subordinated to administrative and civil enforcement. The water pollution and degradation offences in s. 151 (1)(i)(j) of NWA 36 of 1998 are fault-based. In a water stressed country, this is a subsidy to industry for job creation and poverty eradication as dictated by the DSP– the RDP. However, in the prosecution for water pollution and degradation offenses, the application of the “polluter-pays principle” would negative mens rea. The legal effect is that in any prosecution for water pollution or degradation, to secure conviction, the prosecutor is only expected to prove the acts constituting the offence beyond reasonable doubt. It is thereafter open to the accused to the prove, on scale of probabilities, that he lacked either the dolus or culpa required to ground conviction. Since different cast of players are responsible for environmental protection and criminal prosecution (the National Prosecution Authority), coordination amongst the environmental agency, the prosecuting authority and the police is recommended. This can be achieved, inter alia, through joint participation in national enforcement conferences and joint participation in environmental task forces.
Thesis (LL.M. (Environmental law and Management)) --University of Limpopo, 2007.
Keywords: Law; Water; Water law and legislation -- South Africa